2023
DOI: 10.1002/admt.202300377
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on 3D Printing of Structured Porous Materials and Their Applications

Abstract: Porous materials play an essential role in chemical processes such as catalysis, adsorption, and in emerging technologies for electronic materials, light harvesting, and energy transfer. By far, zeolites have contributed most to industrial development. Other porous solid such as activated carbon, metal–organic frameworks, covalent organic frameworks, and porous coordination polymers also have been studied by researchers in the past two decades. The use of porous solids is set to grow in the future, and so is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 131 publications
0
8
0
Order By: Relevance
“…5,6 Different methods for the additive manufacturing of porous materials have been presented in recent years. 7 In short, there are three main categories: extrusion, photopolymerization and powder-based methods. In extrusion-based methods, slurries containing (structured) porous materials are deposited to form porous architectures.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…5,6 Different methods for the additive manufacturing of porous materials have been presented in recent years. 7 In short, there are three main categories: extrusion, photopolymerization and powder-based methods. In extrusion-based methods, slurries containing (structured) porous materials are deposited to form porous architectures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In general, PIPS-based photopolymerization methods are the most versatile in terms of geometric freedom and still offer a wide range of materials with the lowest effort in postprocessing. 7 PIPS is most commonly used in the fabrication of porous thermoset materials, usually epoxy-based porous monoliths. 8−11 Here, it was found that the type and amount of porogenic solvents, as well as the monomer ratios and concentrations, play an important role in the pore structure obtained in the finished porous part.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, tremendous efforts are devoted to developing highly efficient photoinitiating systems activable under visible light. Indeed, photopolymerization is used in a wide range of applications of photopolymerization from coatings and varnishes, adhesives, solvent-free paints and dental restoration materials to 3D/4D printing and microelectronics [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. If the reactivity of photoinitiators remains the main parameter governing the design of new structures, their toxicities and biocompatibilities are more and more regarded [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%